FEATURES OF THE TECHNOLOGY OF GROWING BROCCOLI CABBAGE - N. A. Xudoyberdiyeva; N. J. Nurmatov (Web of Journals Publishing, 2024)
In this article, information on the peculiarities of obtaining a high and high-quality yield of broccoli cabbage by controlling its growth and development, taking into account its attitude to the complex of environmental conditions.
Keywords: Broccoli cabbage, complex of environmental conditions, transitional crop, biotic factors, lighting, temperature, planting scheme, soil fertility.